Undue Influence as a Civil Law Concept in the Hungarian Legislation and Judicial Practice (Investigation of the Drafts of the Hungarian Civil Code between 1900 and 1928 and the Corresponding Literature and Practice) - Réka Pusztahelyi (Journal on European History of Law, 2023)
At the very beginning of the twentieth century, during the period of heightened endeavours for the codification of the private law in Hungary, not only the influence of the “great” civil codes (BGB, ABGB, ZGB) was observable. This paper aims to demonstrate the special impact (or, unique renaissance) of the English equity doctrine of undue influence, among the invalidity rules concerning juridical acts, contracts or testaments. Since this examination cannot be carried on separately from scrutinising the legal thoughts and legislation on immoral and usurious contracts, after some general remarks, this work deals with relevant issues of the Hungarian legislation of usury, independently of civil code drafts or embedded into them. Then, it demonstrates the emergence of the undue influence doctrine in the academic discussion, in the civil code drafts and parallelly, in judicial practice. At this point, we should highlight the special interplay between these “sources of legal thinking”, and as a consequence, how the approach to the notion of undue influence was forming in that period, alongside the draft texts (from the year 1900) up to the Proposal for a Private Law Bill (Private Law Bill, 1928). Although this writing focuses on invalidity issues of contractual transactions, one chapter is dedicated to showing the development of the concept of undue influence relating to testamentary dispositions.